CHARACTERIZATION OF A NOVEL AVIAN AVULAVIRUS 1 OF CLASS I ISOLATED FROM A MUTE SWAN (CYGNUS OLOR) IN MACEDONIA IN 2012 - Aleksandar Dodovski; Zagorka Popova; Vladimir Savić (Sciendo, 2019)
Avian avulavirus type 1 (AAvV-1) belongs to the family Paramyxoviridae, genus Avulavirus. Even though belonging to a single serotype, there is great genetic variability between these viruses. On the basis of the available complete fusion (F) gene and whole genome sequences and using the genotype classification system, AAvV-1 viruses are divided in two major groups: class I and class II. Class I viruses are predominantly avirulent viruses and majority of the isolations come from waterfowl and domestic poultry from live bird markets in USA and China although isolations from wild birds are reported globally. In our study we used classical, molecular and phylogenetic tools to characterize an AAvV-1 isolated from a mute swan in Macedonia. Based on the complete F gene sequence, we have concluded that the virus designated as AAvV-1/mute swan/Macedonia/546/2012 (KP123431) belongs to the class I of AAvV-1 with an avirulent cleavage site motif 112ERQER*L117. The virus could not be assigned to any of the four currently existing subgenotypes (1a, 1b, 1c or 1d) of the single genotype 1 of class I viruses. Two distant viruses, isolated from goose in Alaska in 1991 and from goose in Ohio in 1987, shared the highest nucleotide sequence identity of the complete F gene with the isolate in our study: 92.7% and 92.8%, respectively. This is the first report of isolation of class I AAvV-1 in Southeastern Europe. The asymptomatic nature and the underreporting of sequences from the class I viruses impede the understanding of the molecular epidemiology and evolution of this group of viruses.
Keywords: AAvV-1, class I, mute swan, Macedonia